The Liver Function of Bali Cattle Reared in Garbage Dump - Anak Agung Sagung Kendran; Nyoman Sadra Dharmawan; Ida Bagus Komang Ardana; Luh Dewi Anggreni (Journal of Veterinary and Animal Sciences, 2017)
It is important to learn the liver function of Bali cattle reared in landfills. Landfills is an unusual cattle feedlot which in turn will affect the physiological condition of the animals. Early detection of the animal physiological condition through blood plasma examination is one way to determine the animal liver function. This study used 30 Bali cattle reared in landfills (TPA) Suwung South Denpasar. Blood samples were collected aseptically from the 30 Bali cattle and the activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were detected using Refloton test method. Data were analyzed using One Sample T Test. The results showed that activity of ALT was significantly lower (P<0.01) compared to standard ALT value. Whilst the AST was in the range of normal value. HALT is considered more sensitive in determining the liver function compared to the AST value.